The problem of unilateralism in agency theory: towards a bilateral formulation - Pouryousefi, Sareh; Frooman, Jeff (Cambridge University Press, 2017)
Some business ethicists view agency theory as a cautionary tale – a proof that it is impossible to carry out successful economic interactions in the absence of ethical behaviour. The cautionary-tale view presents a nuanced normative characterisation of agency, but its unilateral focus betrays a limited understanding of the structure of social interaction. This article moves beyond unilateralism by presenting a descriptive and normative argument for a bilateral cautionary-tale view. Specifically, we discuss hat swaps and role dualism in asymmetric-information principal-agent relationships and argue that the norm of reciprocity can function as a moral solution to agency risks in adverse-selection and moral-hazard problems. Our novel bilateral cautionary-tale formulation extends the normative boundaries of the asymmetric-information stream of agency theory, while leaving the fundamental economic assumptions of agency theory intact.